DETERMINANTS OF FORMAL CREDIT ACCESSIBILITY OF VIETNAMESE FARMERS: A CASE STUDY INDAK NONG PROVINCE. - Van, Nguyen (The journal of contemporary issues in business and government, 2021)
Famers are facing a credit constrain which limit them to reinvest on their farming activities. In this context, formal credit plays a major role in their production. This study employs mixed methodology including quantitative and qualitative analysis. Theoretical models have been tested by using analysis of reliability Cronbach’s Alpha, EFA factor analysis, and multiple linear regression analysis. The findings suggest eight factors which significantly impact the accessibility to credit of farmers in Dak Nong province. Asset ownership appears to be an important factor as collateral for their loan applications.